Mitochondria, endothelial cell function, and vascular diseases - Tang, Xiaoqiang; Luo, Yu-Xuan; Chen, Hou-Zao; Liu, De-Pei (Frontiers in Physiology, 2014)
Mitochondria are perhaps the most sophisticated and dynamic responsive sensing systems in eukaryotic cells. The role of mitochondria goes beyond their capacity to create molecular fuel and includes the generation of reactive oxygen species, the regulation of calcium, and the activation of cell death. In endothelial cells, mitochondria have a profound impact on cellular function under both healthy and diseased conditions. In this review, we summarize the basic functions of mitochondria in endothelial cells and discuss the roles of mitochondria in endothelial dysfunction and vascular diseases, including atherosclerosis, diabetic vascular dysfunction, pulmonary artery hypertension and hypertension. Finally, the potential therapeutic strategies to improve mitochondrial function in endothelial cells and vascular diseases are also discussed, with a focus on mitochondrial-targeted antioxidants and calorie restriction.